BOOK REVIEW Bibles in Africa through European eyes - J. Mokhutso (Acta Theologica)
A book review  of "Bibles in Africa through European eyes" by Nyirenda, M. (Bukuru, Hippo Books, 2023) pp. 176, ISBN: 978 1839732522